Raumwirksame Entwicklungseffekte durch Technologieparks: Das südfranzösische Beispiel Valbonne-Sophia-Antipolis - Möller, Hans-Georg (ERDKUNDE, 1985)
Analyzing the example of Valbonne-Sophia-Antipolis (Southern France), this article discusses some effects of regional development that are gained by the establishment and operation of (high) technology parks. In the case of Valbonne-Sophia-Antipolis the objectives of French development policy were as well sectoral, (under the aspect of national economy: modernization of industry) as regional (reduction of inter- and intra-regional disparities). These aims of regional policy are materialized by the choice of a construction-site in the hinterland of the Cote d’Azur, providing a desirable place to live with high qualities for outdoor recreation. The technology park’s peripheral situation implies both a mental and a linear distance to Paris, the national economic and administrative centre. The P.A.C.A. region (Provence, Alpes, Cote d’Azur) offers some research facilities (including universities, state-owned and private research centers) but only few high-technology industries within a clearly under-industrialized region. The technology park’s design and the conditions and restrictions in the use of land are elements representing its evolution from the concept of industrial estates. They have to ensure the park’s functioning and attractivity and to guarantee its compatibility with tourism,the most important economic factor on the Cote d’Azur. Commuting creates an intensive spatial interaction between Valbonne-Sophia-Antipolis and its neighbouring municipalities. Contrary to the objectives of regional planning, the increase of population led to a higher level of urbanization of the Littoral, the densely populated coastal strip. Two other goals of development are far from being realized. By creating high-technology jobs the French inter-regional disparity of research capacity has been reduced, but mainly by migration of researchers and technicians. Local people only supply 42% (1981) of the park’s jobs, working mainly in low-qualified positions. Another problem results from the absence of manufacturing firms in the technology park. The transfer of innovations has therefore until now mainly had a national and international aspect; the impact for the regional economy is only small. The technology park Valbonne-Sophia-Antipolis is dominated by public institutions and interventions. Investment of venture-capital in private manufacturing has still to enlarge the income and employment multipliers.